Comparison of Material Activity and Selectivity in the Electrocatalytic Oxidation of Dibenzothiophene. Issue 11 (29th November 2021) - Kompanijec, Victoria; Swierk, John R.
Abstract : There is an increasing demand for efficient methods to remove sulfur from oil products, such as oxidative desulfurization. In this work, a set of five materials (gold, glassy carbon, nickel, palladium and platinum) were evaluated as electrochemical catalysts for the oxidation of dibenzothiophene (DBT). Bulk electrolysis performed without water present produced DBT dimer, while the addition of 2 M water produced dibenzothiophene sulfoxide (DBTO), both more polar than DBT. LC-MS and NMR were used to characterize the oxidation products. Faradaic efficiencies ranged from 18.4%–56.5% for DBT consumption without water present, and there was a correlation between higher rate constants, lower activation energies, and more efficient DBT oxidation. With water present, selectivity for DBTO formation was highest using gold with a Faradaic efficiency of 87.9%. Group ten metals demonstrated low Faradaic efficiencies due to competitive water oxidation. Though there were differences in the observed selectivity for DBT oxidation, all catalysts reduced the concentration of DBT in solution by similar amounts. Our findings indicate that the overall percent conversion does not give a complete picture of catalytic activity. Of the materials tested, gold was the most selective for oxidation to DBTO, with the presence of water improving the overall reaction activity.